LITERACY AND SENSE MAKING - Murni, Sri Minda; Solin, Mutsyuhito (TABULARASA, 2013)
Copy pasting has been one of the most frustrating phenomena in our academic life. It is found and ranged from studentsâ simple formative paper to end-of-course assignment. This article presents semester 1 studentsâ level of competence in sense making. The data was taken from the documents of studentsâ power point presentation in Literacy class at English Applied Linguistics State University of Medan. Prior to the presentation, the researcher assigned the students to devide the slides into 5 sections, i.e: introduction, connection, application, reflection, and connection as part of problem-based learning design. The findings show that only 33% of the presentations deliver the information completely in these 5 section, while 67% do not. In connection section, which is assigned for thepresentation of the main content of the article, it is found that only 11% of the presentation deliver complete information about the research which include the background (reasons, problems, objectives) of the research, the techniques in collecting data, the theories used to analyze data, the findings, and the discussion, while 89% do not. Analysis on the content of the slides show that only 33% of the presentation put relevant informations, while the rest (66%) do not. Further analysis of the content of the slides show that 66% of the presentations contains copy paste and only 33% represent the sense making ability. The findings imply that the level of the studentsâ ability in sense making is very low. It is suggested to find ways to improve this area of literacy skill by empowering all subjects.